Twintig jaar De Ziener. - Elias, Willem; Exhibition. Twintig jaar De Ziener. Galerie De Ziener Asse. 2007-06-01. 2007-07-11 (Asse : Galerie De Ziener Asse, 2007)
Bogaert, Thomas ; Brouckaert, Hedwig ; Buedts, Raphaël ; Cardon, Marcel ; Coulommier, Julien ; Cuvelier, Werner ; Dilworth, Norman ; Van Doorslaer, Etienne (Maur-Etienne) ; Gees, Paul ; Grard, Chantal ; Lebret, Patrick ; LMG Ploeg ; Mannaers, Werner ; Massart, Jean-Georges ; de Meester, Karel ; Merckaert, Patrick ; De Smedt, Jo ; Vermuyten, Stefaan ; De Vos, Ignace ; Wiels, Jan ; Wyckaert, Maurice
Nederlands
boek